Simplificación de la fertilización de ovocitos durante la producción in vitro de embriones bovinos - Urrego, Rodrigo A.; Tarazona, Ariel M.; Olivera A., Martha; Camargo, Omar (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary This study was conducted to evaluate an in vitro fertilization (IVF) procedure that avoids the washingselection-centrifugation of spermatozoa prior to coincubation with oocytes. A special dish was constructed as follows: in the middle of each of the 4-wells of a conventional plastic dish (larger wells), another little (≈50 μl) glass dish (inner well) was placed (0.3 mm-tall x 0.8 mm in diameter), in such a way that when the larger plate was filled with 700 μl of IVF media (Fert-TALP), the inner well was also filled up to overflowing. Ten in vitro matured oocytes were set into the inner well, and 30 μl of thawed semen were placed on the bottom of the outer well. After one hour of incubation, the media from the outer well was removed, and the well with the remaining media and the germ cells, were incubated for 16 hours. Presumptive zygotes were cultured in a CR1aa media for seven days with a culture media replace at 72 h. As a control, a conventional IVF, using the classical 45-90% Percoll gradient selection, was carried out. The cleavage rates (70.8 vs. 73.1) and the proportion of oocytes reaching morula and blastocyst stages (18.8 vs. 20.3) by the "easy-IVF" were similar to the results obtained by the classical method (p < 0.05). These results indicate that the two methods yield similar results but the "easy-IVF" definitely saves time, human effort, reagents, and after all reduces the manipulation of the sperm with eventual good effects in the long run toward improving in vitro reproduction procedures.